2013
DOI: 10.4321/s1130-01082013000800002
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus -containing probiotic supplementation increases Helicobacter pylori eradication rate: evidence from a meta-analysis

Abstract: Background: Helicobacter pylori infection is recognized as a major contributory factor to many diseases, but recommended eradication therapies demonstrated unsatisfactory eradication rates. Currently, some studies suggested that lactobacillus species have an inhibitory action on Helicobacter pylori both in vitro and in vivo.Objective: this meta-analysis broadly examined the efficacy of eradication regimens supplemented with lactobacillus-containing probiotic on eradication rates and side effects.Methods: eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0
21

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 41 publications
6
73
0
21
Order By: Relevance
“…Several studies showed that an administration of bismuth in quadruple therapy increased the eradication rate of H. pylori to approximately 90%, significantly better than of standard triple therapy (Ford et al, 2008, Fock et al, 2009). In addition, recent studies have demonstrated that adding probiotic supplement to standard triple therapy significantly enhanced the H. pylori eradication rate (Mirzaee and Rezahosseini, 2012, Zheng et al, 2013, Wang and Huang, 2014. Thus far, the efficacy of H. pylori eradication by adding bismuth and probiotic to standard triple therapy has not been reported.…”
Section: Table 3 Adverse Events According To 4 Treatment Regimensmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies showed that an administration of bismuth in quadruple therapy increased the eradication rate of H. pylori to approximately 90%, significantly better than of standard triple therapy (Ford et al, 2008, Fock et al, 2009). In addition, recent studies have demonstrated that adding probiotic supplement to standard triple therapy significantly enhanced the H. pylori eradication rate (Mirzaee and Rezahosseini, 2012, Zheng et al, 2013, Wang and Huang, 2014. Thus far, the efficacy of H. pylori eradication by adding bismuth and probiotic to standard triple therapy has not been reported.…”
Section: Table 3 Adverse Events According To 4 Treatment Regimensmentioning
confidence: 97%
“…The CYP2C19 genotype testing was performed according to previously described technique (Zheng et al, 2013), and the results were expressed as: rapid metabolizer (RM), intermediate metabolizer (IM) or poor metabolizer (PM). The presence of H. pylori was defined as: 1) positive H. pylori culture, or (2) two positive tests (rapid urease test and histology).…”
Section: The Diagnosis Of H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the demonstration of anti-H. pylori activity of probiotics such as Lactobacillus, Saccharomyces boulardii, and Bifidobacterium, in in vitro and experimental models of H. pylori infection (19), probiotics have been suggested to improve H. pylori eradication and reduce side effects during therapy (17,20,21). However, findings from clinical studies on the use of probiotics as an adjuvant therapy to H. pylori infection have been inconsistent, with the demonstration of reduced side effects of antibiotics and improved eradication rates in some studies (16,(22)(23)(24)(25)(26)(27)(28)(29)(30), while no significant effects of adjuvant probiotics on eradication rates (22,(31)(32)(33)(34)(35)(36) or side effects (26,27,30,31,32,33,(35)(36)(37) have been reported in other studies.…”
mentioning
confidence: 98%
“…Были опубликованы 11 метаанализов по оценке эффективности пробиотиков в качестве вспомогательных веществ для антибиотиков для эрадикации Нр [31][32][33][34][35][36][37][38][39][40][41][42]. Все исследования обнаружили, что добавление пробио-тика в схемы антибиотикотерапии увеличивает эффек-тивность лечения с отношением шансов в пределах от 1,12 до 2,07.…”
unclassified